Leaf-Impression and Palaeoscientific Study of Siwalik-belt of Koilabas in Western Nepal: Part-2 - Neetu Chandra, Pateshwari Prasad Tripathi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In this work, we present well-preserved leaf-impression of fourteen species of angiosperm. These leaf-impressions were also searched from Siwalik belt of Koilabas in Western Nepal. The study shows that above fourteen species belonging to twelve genera and seven family of dicotyledon. Above study alongwith already known data reflect palaeoecology and phytogeography of area which shows Miocene-Pleistocene age in the Himalayan foot hills. These studies further signify the physiogenomic characters of fossil?s leaves with climate.